Analisis Efektivitas Metode Pembelajaran Discovery Inquiry dalam Pelajaran Sejarah di MAS Pringgasela - M. Alpan Hadi; Armin Subhani; Abdul Rasyad (Educatio, 2026)
The main concept of this study highlights the implementation of the Discovery Inquiry model as an innovative approach to enhance students’ critical and reflective thinking skills in history learning. This research, conducted at MAS Pringgasela, aims to describe how the model promotes active learning, independent exploration, and conceptual understanding of historical events. The findings show that Discovery Inquiry transforms classroom dynamics—students who were previously passive become more engaged in discussions, group analyses, and drawing historical conclusions. However, the implementation of this model still faces challenges such as limited instructional time, low literacy skills, and insufficient learning media and resources. To address these issues, this study offers solutions through more flexible inquiry stages, teacher capacity development, and the provision of alternative learning resources. These findings align with Bruner’s theory of discovery learning while providing new insights by situating it within the Islamic-based madrasa education context. Overall, this study emphasizes that Discovery Inquiry is not merely a learning model but a meaningful pedagogical strategy that fosters critical thinking, collaboration, and character formation—essential values in transformative history education.